Feri Lainšček and His Poetry for Children and Youth - Radetič, Andreja (International Journal of English Literature and Social Sciences (IJELS), 2019)
The article attempts to briefly review Feri Lainšček’s children’s poetry. After short bibliography, some of the reasons for the author’s popularity with young readers are mentioned. Later on, the themes of his youth poetry and illustrations in his collections are analysed.